Masterpiece mystery. Death comes to Pemberley [videorecording (DVD)] - Rhys, Matthew, 1974-; Maxwell Martin, Anna, 1977-; Goode, Matthew, 1978-; Coleman, Jenna, 1986-; James, P. D. (2014)
Elizabeth and Darcy, now six years married and with two young sons, are preparing for the lavish annual ball at their magnificent Pemberley home.